2012
DOI: 10.4097/kjae.2012.62.3.251
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of intravascular insertion in thoracic epidural catheterization by using real time fluoroscopy

Abstract: BackgroundEpidural analgesia is commonly used to provide several types of pain relief. Although this technique has been widely used with many advantages, currently the complications appear to be increasing. Especially, inadvertent intravascular cannulation and intravascular local anesthetic administration can lead to fatal consequences.MethodsData was collected on 296 patients undergoing elective thoracic or abdominal surgery. Two detection methods were utilized to confirm the epidural intravascular cannulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Furthermore, fluoroscopy allows the operator to detect inadvertent catheter positioning in the intrathecal space, subdural space, and blood vessels. 39 Unfortunately, in many centers, the additional equipment, manpower (radiology technologist), and radiation exposure often curtail its routine use in surgical and obstetrical patients.…”
Section: Radiographic Imagingmentioning
confidence: 99%
“…Furthermore, fluoroscopy allows the operator to detect inadvertent catheter positioning in the intrathecal space, subdural space, and blood vessels. 39 Unfortunately, in many centers, the additional equipment, manpower (radiology technologist), and radiation exposure often curtail its routine use in surgical and obstetrical patients.…”
Section: Radiographic Imagingmentioning
confidence: 99%
“…Reports have indicated the incidence of paresthesia during the epidural catheter insertion from 44% [8] to as high as 57% in pregnant mothers [9]. In addition, the prevalence of unintentional vascular puncture with radiologic confirmation has been reported at 1.4% [10]. In this study, the reported cases of paresthesia in the cephalad and caudad groups were 15.5% and 18.4%, respectively.…”
Section: Discussionmentioning
confidence: 55%
“…14,16,22 However, its use is labor and time intensive, requires additional equipment and often manpower, and exposes the patient and medical personnel to radiation.…”
Section: Discussionmentioning
confidence: 99%